2013
DOI: 10.1371/journal.pone.0072557
|View full text |Cite
|
Sign up to set email alerts
|

SNP Association Mapping across the Extended Major Histocompatibility Complex and Risk of B-Cell Precursor Acute Lymphoblastic Leukemia in Children

Abstract: The extended major histocompatibility complex (xMHC) is the most gene-dense region of the genome and harbors a disproportionately large number of genes involved in immune function. The postulated role of infection in the causation of childhood B-cell precursor acute lymphoblastic leukemia (BCP-ALL) suggests that the xMHC may make an important contribution to the risk of this disease. We conducted association mapping across an approximately 4 megabase region of the xMHC using a validated panel of single nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…To date GWAS have provided no evidence implicating immune response gene variants, as might have been anticipated from infection-based hypotheses for the aetiology of ALL. However, prior studies examining major histocompatibility complex (HLA) genes [76][77][78] , interferon-γ (IFNG) 79 , Toll-like receptor 6 (TLR6) 80 or the presence and/or absence of specific killer-cell immunoglobulin-like receptor (KIR) family genes 81 did record significant associations with particular allelic variants. Notably, TLR6 variants and KIR genes were associated with decreased risk of all childhood ALL.…”
Section: Inherited Susceptibilitymentioning
confidence: 99%
“…To date GWAS have provided no evidence implicating immune response gene variants, as might have been anticipated from infection-based hypotheses for the aetiology of ALL. However, prior studies examining major histocompatibility complex (HLA) genes [76][77][78] , interferon-γ (IFNG) 79 , Toll-like receptor 6 (TLR6) 80 or the presence and/or absence of specific killer-cell immunoglobulin-like receptor (KIR) family genes 81 did record significant associations with particular allelic variants. Notably, TLR6 variants and KIR genes were associated with decreased risk of all childhood ALL.…”
Section: Inherited Susceptibilitymentioning
confidence: 99%
“…This haplotype block spans the BRD2 locus, which has been associated with Juvenille Epilepsy, and is not an obvious candidate risk factor for ALL, despite its relatively wide expression pattern [31]. Taken in combination with published data from the California Childhood Leukemia study [19], and the results of LDsplit analyses which indicate multiple cis-acting sequences, including loci identified in the SNP association studies, contributing to recombination at DNA3 , this is suggestive of an association of these haplotypes and recombination events affecting HLA-DOA , with BCP-ALL. HLA-DOA encodes one component of the heterodimeric HLA-DO molecule, a non-classical HLA molecule which contributes to the antigen-recognition repertoire of CD4+ T-cells through influencing intracellular peptide loading by HLA-DM by acting as a substrate mimic [32].…”
Section: Discussionmentioning
confidence: 85%
“…However, a modest (non-significant) association with the SNP rs3135034, approximately 97 kb centromeric of HLA-DPB1 , was reported in a UK GWAS [18] . Furthermore, an independent SNP analysis of the extended MHC (xMHC) in a California ALL study revealed a significant association with rs9296068, located approximately 60 kb centromeric of HLA-DPB1 [19] . The SNPs identified in these two studies are in close proximity to each other (∼37 kb apart) and flank the HLA-DOA locus.…”
Section: Introductionmentioning
confidence: 99%
“…To address this, comprehensive examination of genetic variability of the entire xMHC, including high-resolution HLA allelic typing, is needed and is currently achievable using recently developed technologies. High-density MHC SNP genotyping studies, two of which were described in this review (23, 57), are a step in this direction, but they lacked direct allelic typing of all classical HLA loci. The UKCCS applied previously derived methods (71, 72) to impute HLA alleles based on GWAS-derived SNPs for six of the nine classical HLA loci.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a high-density SNP analysis of the MHC region in the NCCLS was conducted (57). In single SNP analyses this study identified one locus, rs9296068, as significantly associated with BCP-ALL risk after correction for multiple testing (OR = 1.40, 95% CI = 1.19–1.66, corrected p -value = 0.036).…”
Section: Xmhc Association Mapping Studiesmentioning
confidence: 99%